Regulasi dan Etika dalam Penggalangan Donasi Online (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2026)
The internet has penetrated various aspects of human life, changing the way individuals interact with one another. Everything from reading the news and searching for information to working and studying, to fundraising, can now be done online. Fundraising, often referred to as donations, can now be done through social media. People can contribute their funds online, a process known as crowdfunding. Crowdfunding is an internet-based funding method that allows certain initiatives to be funded through contributions from many people online, without any specific time limits. This fundraising generally focuses on social, educational, or humanitarian initiatives. In Indonesia, fundraising is often carried out by non-profit organizations or individuals. The success of a fundraising campaign is influenced by several factors, such as clarity of campaign objectives and a compelling narrative to attract donors. However, fundraising is still vulnerable to abuse by irresponsible parties. Therefore, regulations in Indonesia need to be strengthened to prevent abuse and increase accountability. Rules related to fundraising are regulated in Law of the Republic of Indonesia Number 9 of 1961 concerning the Collection of Money or Goods. Thus, optimizing fundraising requires a combination of effective communication strategies, transparent management, and clear regulations. The results of this study are expected to serve as a guide for organizations and individuals seeking effective fundraising, as well as provide input for policymakers regarding fundraising regulations in Indonesia.